Urban transport policy transfer in Central and Eastern Europe. - Stead, Dominic; De Jong, Martin; Reinholde, Iveta (TH Zürich, NSL, 2008)
Der Beitrag befasst sich mit dem internationalen Policy-transfer anhand des Exports westeuropäischer Stadtverkehrsmodelle (Bremen und Karlsruhe) nach Warschau und Riga, die Hauptstädte zweier mittel- und osteuropäischer Beitrittsländer. Es handelt sich um Fälle, bei denen "importierende" und "exportierende" Länder vollkommen unterschiedliche gesellschaftliche, wirtschaftliche und institutionelle Ausgangsbedingungen haben. Die Beispiele lassen erkennen, dass ein erfolgreicher Policy-transfer weit mehr verlangt als ein einfaches Kopieren oder Nachahmen. Der Beitrag zeigt: Um Erfolge in den Städten Mittel- und Europas zu erzielen, sind groß angelegte institutionelle Transformationen weder machbar noch wünschenswert. Kleine Initiativen mit überschaubaren, vergleichsweise kurzfristig erzeilbaren Ergebnissen und mit moderatem finanziellem Aufwand arbeiten häufig besser und entwickeln eine größere Eigendynamik in Richtung einer Nachhaltigkeit städtischer Verkehrssysteme. goj/difu

European Territorial Cooperation is one important context in which partners from across the whole of Europe meet and learn from each other. Naturally, the involvement of partners from Central and Eastern European (CEE) countries in this process is increasing as a consequence of the expansion of Europe, particularly the accession of ten new EU member states in 2004, and two more in 2007. Various examples can be found where CEE countries are seeking to catch up politically and economically by drawing lessons from policies in more developed countries. The uncertainties of policy-making in some of these countries have made policy transfer a particularly attractive option, as politicians see it as the quickest solution to many problems without having to reinvent the wheel. This paper focuses on international policy-transfer and lesson-drawing, looking specifically at how urban transport concepts and ideas have been transferred from Western Europe to two CEE countries. In these cases, the social and economic situations in the "borrowing" and "lending" countries are very different. So too, are the institutional frameworks. As a consequence, successful policy transfer is much more complex than mere copying or emulation. The paper argues that large-scale institutional transformations are neither nor desirable to produce results that benefit cities in CEE countries. Small initiatives with straightforward, comparatively short-term outcomes and moderate budgets often work better and keep momentum going for further steps towards more sustainable urban transport policies and programs. difu
Keywords: Raumplanung; Verkehrsplanung; Stadtverkehr; Verkehrspolitik; Planungsprogramm; Planungsmodell; Verkehr; Planungskooperation; Grenzüberschreitung; Grenzüberschreitende Zusammenarbeit; Grenzüberschreitende Planung; Europäische Zusammenarbeit; Transformation; Transfer